Dynamic Clusters Supported Bi-Level Control System With Lower Communication Requirements for a Distribution Network With Distributed Battery and Photovoltaic Systems - Zhang, Runfan; Liu, Zixuan; Bie, Zhaohong; Hredzak, Branislav (IEEE transactions on smart grid, 2024)
This paper proposes a bi-level control framework for dynamic microgrid clusters in a distribution network with distributed photovoltaic and battery storage systems. The proposed bi-level control framework comprises interactive secondary and tertiary level control systems. A distributed event-triggered mechanism is proposed for the secondary level control of each dynamic microgrid cluster to achieve frequency and voltage regulation and balancing of the state of charge of battery storage systems within the cluster. At the tertiary level, a receding horizon model predictive control is implemented to minimize transmission power losses and battery storage systems losses by providing optimal battery storage systems output powers and the voltage source converters output voltages, with a one-minute interval. The secondary level control is modified to implement the optimal solutions provided by the tertiary level model predictive control. Furthermore, the secondary level distributed event-triggered control minimizes unnecessary data transmission by introducing a time delay, resulting in a reduced communication burden. The proposed bi-level control framework is validated in real-time on a modified IEEE 13-node test feeder using RTDS with the tertiary level model predictive control solved on a computer via the hardware-in-loop method.